High Performance Thin Layer Chromatography and High Performance Liquid Chromatography determination of Quercetin from Polyalthia longifolia leaves - Mahesh Doshi, Gaurav; Devidas Une, Hemant (Free Radicals and Antioxidants)
Introduction: Polyalthia longifolia Thwaites (PL) is an ornamentally important flowering tree with immense potential. Identification of phytochemical constituents from plant extracts is need of hour in developing countries like India. These elucidated constituents may play a pivotal role in providing remedies to plethora of diseases whether major or minor. Proper application of analytical technique is key to success in interpretation of these plant constituents. Flavanoids are widely noticeable in number of plant extracts. Flavonols class of compound like quercetin has been reported to possess good amount of ethno-pharmacological relevance from number of medicinally as well as local plants. Objective: In present research studies the aim was to find out by chromatographic techniques how much was percentage of quercetin present in the Polyalthia longifolia Thwaites leaves ethanolic extract. Materials and Methods: Polyalthia longifolia Thwaites leaves after ethanolic extraction and preliminary phytochemical studies were subjected to identification of quercetin by high performance thin layer chromatography (HPTLC) and high-pressure liquid chromatography (HPLC). Results: Preliminary phytochemical evaluation confirmed the presence of flavonoids. The Rf value of the extract was found to be conceding with the standard quercetin by using analytical techniques. Quercetin was found to be 84.26% w/w and 74.45% w/v by high performance thin layer chromatography (HPTLC) and high-pressure liquid chromatography (HPLC) respectively. Conclusion: The active constituent identified from Polyalthia longifolia Thwaites leaves extract was found to be identical to quercetin.
Keywords: HPLC; HPTLC; Polyalthia longifolia; Quercetin; TLC